Berdamai dengan Pluralitas Paham Keberagamaan - Biyanto Biyanto (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
The article asserts that plurality—particularly with respect to religious understanding—is a certainty and an avoidable matter, which should be wisely addressed. This is a pivotal issue as the fact shows us that Indonesia, naturally and culturally, consists of various different ethnic groups. Bhinneka Tuggal Ika—as national watchword—affirms that Indonesia is founded on diversity and difference. However, the Indonesian nation has to unite despite its diversity. In addition, Indonesia is also called a colourful state. This statement refers to the fact that there are a vast number of different ethnic groups, cultures, and religions that live and exist in this country. Empirically, plurality has often caused social conflicts which involve interfaith groups with different religious understanding. The conflict occurs when these different groups are unprepared to live together harmoniously and build coexistence. Therefore, it is important to continuously promote the values of pluralism and multiculturalism in order to create a better life order based on acceptance, respect, and tolerance. To do so, emotional and intellectual intelligence—as “social modal”—are urgently required. The writer argues that this is a way—if not the sole—to bring about a solution to the problem of religious plurality and religious understanding.